2015
DOI: 10.1155/2015/860381
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Content and Elemental and Phytochemical Analyses ofMoringa oleiferaGrown in Mexico

Abstract: Moringa oleiferais a tree distributed in Mexican semiarid and coastal regions.M. oleiferais used in practice in the treatment of various diseases and is available without a medical prescription, often in the form of an herbal infusion for everyday use. The aim of the present study was to evaluate the chemical composition and nutritional values of driedM. oleiferaleaf powder collected from two different regions in Mexico. All samples ofM. oleiferaexhibited moisture levels varying from 3.06 to 3.34%, lipids from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
83
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 56 publications
(59 reference statements)
12
83
2
3
Order By: Relevance
“…More recently, HPLC-DAD-ESI_MS/MS analysis carried out by Karthivashanet al [52] confirmed the presence of multiflorin-B, apigenin-8-C-glucoside, quercetin and kampferol derivatives in crude hydroethanolic extract of M. oleifera leaves. Similarly, 7 polyphenols namely; gallic acid, chlorogenic acid, luteolin, rutin, quercetin, kampferol and apigenin were identified in methanolic extract of M. oleifera by HPLC analysis [53]. Also, reproductive and vegetative tissues of M. oleifera leaves and stem were found to have quinic acid, quercetin and kampferol [54].…”
Section: Ability Of M Oleifera To Induce Apoptosis In Cancer Cellsmentioning
confidence: 95%
“…More recently, HPLC-DAD-ESI_MS/MS analysis carried out by Karthivashanet al [52] confirmed the presence of multiflorin-B, apigenin-8-C-glucoside, quercetin and kampferol derivatives in crude hydroethanolic extract of M. oleifera leaves. Similarly, 7 polyphenols namely; gallic acid, chlorogenic acid, luteolin, rutin, quercetin, kampferol and apigenin were identified in methanolic extract of M. oleifera by HPLC analysis [53]. Also, reproductive and vegetative tissues of M. oleifera leaves and stem were found to have quinic acid, quercetin and kampferol [54].…”
Section: Ability Of M Oleifera To Induce Apoptosis In Cancer Cellsmentioning
confidence: 95%
“…Proteins are a very important class of biomolecules needed for maintenance and repair of body tissues, synthesis of vital hormones and an alternative source of energy when there are deficiencies of other rich sources. The protein content of Irvingia gabonensis O'Rorke Baill leaf from this study (11.43±1.07 %), is high when compared to that of Talinum triangulare leaves (3.52±0.32) [22], Moringa oleifera leaves (10.74 ± 1.3) [26], but low when compared to Annona muricata leaves (25.00 ± 0.06) [25]. Irvingia gabonensis O'Rorke Baill leaf may therefore be considered a good source of protein.…”
Section: Discussionmentioning
confidence: 52%
“…It helps in regulating plasma volume and acid-base balance, vital in the maintenance of osmotic pressure of the body fluids, helps in preserving normal irritability of muscles and cell permeability, activates nerve and muscle function and involved in Na + /K + -ATPase, maintains membrane potentials, helps in transmission of nerve impulses and the absorptive processes of monosaccharides, amino acids, pyrimidines, and bile salts [35]. The sodium content of Irvingia gabonensis O'Rorke Baill leaf obtained from this study (93.11±0.04 mg/100g), is high compared with Chromolaena odorata leaf [37], Annona muricata leaves (69.49mg/100g) [25], and Vernonia amygdalina leaves (48.31mg/100g) [38] and Moringa oleifera leaves [26]. With respect to FAO/WHO recommended daily intakes, the results obtained from this study indicates that Irvingia gabonensis O'Rorke Baill leaf is rich in zinc and iron but low in magnesium [36].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In Philippines, Cambodia, Central and North America [22]. M. oleifera is known as drumstick in English [15,16,17,18,23,24,25,26,27], Zogale in Hausa [26,27,28], "Eweigbale" in Yoruba [26], Okweoyibo in Igbo [26]. M. oleifera is a small, fast growing evergreen or deciduous tree that usually grows up to 10-12m in height [16,18,24,25,28].…”
Section: Introductionmentioning
confidence: 99%